APLIKASI TEKNOLOGI BIOENGINEERING JEBAKAN SEDIMEN DI SUB DAS CITANDUY HULU - Soewandita, Hasmana; Sudiana, Nana (Center for Environmental Technology, 2009)
Citanduy watershed Ã‚Â has been classified as a critical watershed in West Java. Sedimentation load at Citanduy watershed reach 5 milion cubic meters/years.Ã‚Â It is indicated that lagoon area Ã¢â‚¬Å“Segara AnakanÃ¢â‚¬Â was decreased about 823 hectars. Land use changes for cultivation area at Citanduy upland causes acceleration Ã‚Â land degradation. Various efforts of the civil engineering and vegetative approach have been applied to control Ã‚Â erosion and sedimentation. Alternative technology forÃ‚Â controlling soil erosion and sedimentation is the application of sediment trap bioengineering.Ã‚Â It is application on micro catchment area, environment-friendly, and easily adapted for the farmers community.Ã‚Â The main for material of bioengineering sediment trap isÃ‚Â made ofÃ‚Â Bamboo. Results of design that is applied in the critical area at BukitÃ‚Â Bitung up land (Citaduy upland) Kecamatan Tambaksari, Ciamis Region, measuring the width between 100 cm to 150 cm, whereas the Ã‚Â height are between 80 cm to 100 cm. The application of this technology is effective sediment traps for micro catcment area of <5 hectars. Therefore for Ã‚Â a broad cachment area more sediment traps are required. In a period of not more than 1.5 month, the sediment trapÃ‚Â has been able to capture sediments up to 1 m3 per unit. The performance of sediment traps bioengineering also shown that bamboo as main components has grown up to not more than 30 days. The trapped sediments were restored back to the land for agricultural purposes after being add by agricultural waste. Sediments that have been processed at the same time also functions as soil amelioration or soil improvement.Ã‚Â Key words : degradasi lahan, jebakan sedimen, bioengineering, sedimentasi, ameliorasiÃ‚Â